Formulation Optimization of Arecoline Patches - Pao-Chu Wu; Pi-Ju Tsai; Shin-Chen Lin; Yaw-Bin Huang (The Scientific World Journal)
The response surface methodology (RSM) including polynomial equations has been used to design an optimal patch formulation with appropriate adhesion and flux. The patch formulations were composed of different polymers, including Eudragit RS 100 (ERS), Eudragit RL 100 (ERL) and polyvinylpyrrolidone K30 (PVP), plasticizers (PEG 400), and drug. In addition, using terpenes as enhancers could increase the flux of the drug. Menthol showed the highest enhancement effect on the flux of arecoline.